2012
DOI: 10.1200/jco.2011.36.9868
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FLT3 Internal Tandem Duplication on the Outcome of Related and Unrelated Hematopoietic Transplantation for Adult Acute Myeloid Leukemia in First Remission: A Retrospective Analysis

Abstract: FLT3/ITD adversely affected the outcome of HSCT in the same direction it does after chemotherapy; despite this, more than half of the patients harboring this mutation who received transplants were alive and leukemia free at 2 years. To further improve the results, use of FLT3 inhibitors before or after HSCT deserves investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
206
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(223 citation statements)
references
References 33 publications
9
206
3
5
Order By: Relevance
“…The lack of significant association between conventional cytogenetics or FLT3 mutations and prognosis in our series, contrary to AML cohorts after first allo-SCT, 26,27 suggests the selection of other adverse biologic factors in these very high-risk patients. Such defects, like the loss of HLA heterozygosity in leukaemic blasts, were recently demonstrated by more sensitive methods, such as genome-wide profiling.…”
Section: Discussioncontrasting
confidence: 40%
“…The lack of significant association between conventional cytogenetics or FLT3 mutations and prognosis in our series, contrary to AML cohorts after first allo-SCT, 26,27 suggests the selection of other adverse biologic factors in these very high-risk patients. Such defects, like the loss of HLA heterozygosity in leukaemic blasts, were recently demonstrated by more sensitive methods, such as genome-wide profiling.…”
Section: Discussioncontrasting
confidence: 40%
“…(1) AML patients with FLT3 gene internal tandem duplication (ITD) have a poor outcome, with a median overall survival of 13.1 months. (2) Although AML patients with FLT3-ITD benefit from allogeneic HSCT in first complete remission (CR1), (3) it has been shown that this subset of patients are at increased risk of relapse after HSCT. (3,4) Post-transplant relapsed AML is associated with a high mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Although AML patients with FLT3-ITD benefit from allogeneic HSCT in first complete remission (CR1), (3) it has been shown that this subset of patients are at increased risk of relapse after HSCT. (3,4) Post-transplant relapsed AML is associated with a high mortality rate. The use of chemotherapy followed by donor lymphocyte infusion (DLI) can provide long-term remission in less than 20% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although direct comparisons are limited, outcomes after alloHCT generally compare favorably to chemotherapy-based approaches with overall survival (OS) at two or more years as high as 60%, although results are variable. [2][3][4][5] Unfortunately, many patients lack a suitable HLA-matched donor, precluding alloHCT consolidation. Umbilical cord blood (UCB) transplantation provides an alternative donor source for alloHCT and has given promising results in many hematologic malignancies.…”
mentioning
confidence: 99%
“…1 FLT3-ITD + AML is associated with an increased risk of relapse and shorter overall survival. 1,2 Because of this, allogeneic hematopoietic cell transplantation (alloHCT) has been commonly used for consolidation of FLT3-ITD + AML patients. Although direct comparisons are limited, outcomes after alloHCT generally compare favorably to chemotherapy-based approaches with overall survival (OS) at two or more years as high as 60%, although results are variable.…”
mentioning
confidence: 99%